1998
DOI: 10.1046/j.0909-8836.1998.eos106205.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triclosan on interleukin‐1β production in human gingival fibroblasts challenged with tumor necrosis factor α

Abstract: The effect of the dentifrice ingredient triclosan (2,4,4'-trichloro-2'-hydroxyldiphenyl ether) on the production of interleukin (IL)-1beta and IL-6 was studied in human gingival fibroblasts challenged with tumor necrosis factor alpha (TNFalpha) in vitro. When gingival fibroblasts were treated simultaneously with triclosan (0.25, 0.5 microg/ml) and TNFalpha (10 ng/ml), the stimulatory effect of TNFalpha on IL-1beta production was reduced by the agent. In situ hybridisation showed that the TNFalpha-induced expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…There have been recent developments into the incorporation of a triclosan-containing composite which is proposed for use in restorative resins and has demonstrated some antibacterial activity against common oral bacteria (Rathke et al 2010). As triclosan has previously been shown to have anti-inflammatory properties (Mustafa et al 1998), in addition to its effectiveness against oral bacteria, this makes it an attractive biocide for potential use in endodontic treatments as it may promote the natural repair processes of the tooth, as previously described (1.2.3). However, the results from this study have shown that triclosan alone is not effective at complete eradication of SAG bacteria, which could lead to problems in endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been recent developments into the incorporation of a triclosan-containing composite which is proposed for use in restorative resins and has demonstrated some antibacterial activity against common oral bacteria (Rathke et al 2010). As triclosan has previously been shown to have anti-inflammatory properties (Mustafa et al 1998), in addition to its effectiveness against oral bacteria, this makes it an attractive biocide for potential use in endodontic treatments as it may promote the natural repair processes of the tooth, as previously described (1.2.3). However, the results from this study have shown that triclosan alone is not effective at complete eradication of SAG bacteria, which could lead to problems in endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most commonly used pulp capping treatment but in recent years there has been an increased interest in novel antimicrobials in for use in endodontic treatments and dentifrices. Due to the inflammatory nature of pulpitis there has been particular interest in antimicrobials that have also been identified as having anti-inflammatory properties, such as triclosan and certain naturally expressed proteins known as antimicrobial peptides (AMPs) (Mustafa et al 1998;Yang et al 2002).…”
Section: 'Photosynthesise' By Frank Turnermentioning
confidence: 99%
See 1 more Smart Citation
“…Grids were placed on a thin formvar film, and the film was placed on a slide and processed as the semithin sections. The slides were developed and examined by light microscopy (LM) and TEM for cells containing 14 C-triclosan (cells with silver grains). Cells treated with unlabeled triclosan (1 mg/mL) were used in parallel as negative controls.…”
Section: C-triclosan By Autoradiographymentioning
confidence: 99%
“…12,13 In addition, we reported that triclosan reduces the production of IL-1b and interferon-g (IFN-g) as well as the expression of major histocompatibility complex (MHC) class II in gingival fibroblasts. 14,15 However, the effect of triclosan on the signal pathways involved in the production of inflammatory mediators in gingival fibroblasts is not well known. The knowledge of intracellular uptake and distribution of triclosan is crucial to understand the mechanism(s) involved in its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%